Clinical utility of a traditional score system for the evaluation of the peritoneal dialysis exit-site infection in a national multicentric cohort study - Rigo, Mariane (2020)
Introduction: Exit-site infection (ESI) is an important risk factor for peritonitis in patients under chronic peritoneal dialysis (PD). The International Society for Peritoneal Dialysis (ISPD) recommend its diagnosis as the presence of purulent drainage in the exit site (ES) but time-consuming scores using others skin signs are routinely used. Objective: To investigate the correlation between the diagnosis of ESI with a score based on five clinical signs obtained from ES inspection, and also if there are interaction with patient’s race. Methods: Multicenter and prospective cohort. We included adult patients from 122 clinics, incident on PD and with a 12-month stay in therapy. The event of interest was ESI, defined as purulent drainage. The clinical score used was composed of hyperemia, edema, pain, scab, and granuloma. Statistical analysis was performed using multilevel logistic regression model, likelihood test, and Cohen concordance analysis. Results: A total of 35,354 ES assessments were performed during the first year of dialysis in 3297 patients. There was a rate of 10.1 (9.1–11.2) episodes of ESI per 1000 patients/month. In patients with ESI, the prevalence of hyperemia was 55.9%, edema 67.3%, pain 31.8%, and scab 23.2%. The agreement with the score was 60.6% and showed differences according to the patient’s race, being 53.2% for African Americans descendants and 65.4% for others. The use of scales for the diagnosis of ESI does not add much information in addition to the presence of purulent secretion as currently recommended by the ISPD.